Disturbances in beta-cell function in impaired fasting glycemia - van Haeften, T. W.; Pimenta, W.; Mitrakou, A.; Korytkowski, M.; Jenssen, T.; Yki-Jarvinen, H.; Gerich, J. E. (Amer Diabetes Assoc, 2002)
In a cross-sectional study, we assessed beta-cell function and insulin sensitivity index (ISI) with hyperglycemic clamps (10 mmol/l) in 24 subjects with impaired fasting glycemia (IFG, fasting plasma glucose [FPG] between 6.1 and 7.0 mmol/l), 15 type 2 diabetic subjects (FPG >7.0 mmol/l), and 280 subjects with normal fasting glycemia (NFG, FPG <6.1 mmol/l). First-phase insulin release (0-10 min) was lower in IFG (geometric mean 541 pmol/l (.) 10 min; 95% confidence interval [CI] 416-702 pmol/l (.) 10 min) and in type 2 diabetes (geometric mean 376 pmol/l (.) 10 min; 95% CI 247-572 pmol/l (.) 10 min) than NFG (geometric mean 814 pmol/l (.) 10 min; 95% CI 759-873 pmol/l (.) 10 min) (P < 0.001). Second-phase insulin secretion (140-180 min) was also lower in IFG (geometric mean 251 pmol/l; 95% CI 198-318 pmol/l; P = 0.026) and type 2 diabetes (geometric mean 157 pmol/l; 95% CI 105-235 pmol/l; P < 0.001) than NFG (geometric mean 295 pmol/l; 95% CI 276-315 pmol/l): IFG and type 2 diabetic subjects had a lower ISI (0.15 +/- 0.02 and 0.16 +/- 0.02 mumol/kg fat-free mass [FFM]/min/ pmol/l, respectively) than NFG (0.24 +/- 0.01 mumol/kg FFM/min/pmol/l, P < 0.05). We found a stepwise decline in first-phase (and second-phase) secretion in NFG subjects with progressive decline in oral glucose tolerance (P < 0.05). IFG subjects with impaired glucose tolerance (IGT) had lower first-phase secretion than NFG subjects with IGT (P < 0.02), with comparable second-phase secretion and ISI. NFG and IFG subjects with a diabetic glucose tolerance (2-h glucose >11.1 mmol/l) had a lower ISI than their respective IGT counterparts (P < 0.05). We conclude that the early stages of glucose intolerance are associated with disturbances in beta-cell function, while insulin resistance is seen more markedly in later stages.